A standard procedure for dune mapping along the Bulgarian Black Sea coast: an integrated approach combining UAS photogrammetry, geomorphological and phytocoenological surveys - Prodanov, Bogdan; Gussev, Chavdar; Sopotlieva, Desislava; Valcheva, Magdalena; Bekova, Radoslava; Baltakova, Ahinora; Tzonev, Rosen; Popov, Julian (Frontiers in Marine Science, 2025)
Coastal dunes (CD) are dynamic environments shaped by sediment accumulation, sea breeze and vegetation cover, which are also highly sensitive to human intervention. The urbanization of coastal areas, global warming and rising sea levels pose significant threats to CD systems, leading to erosion and habitat loss. In the past decade, the total CD area in Bulgaria has decreased by over 12 hectares, resulting in the complete loss of five dune systems. Over 5% of the CDs along the Bulgarian Black Sea Coast (BBSC) face similar challenges, primarily due to human-induced pressure and alterations in dune landforms. This study introduces a Standard Dune Mapping Procedure (SDMP) for the BBSC based on geospatial data of dune habitats, facilitating the cadastral maps and registers and effective conservation and management activities. The proposed methodology, developed through the collaboration of the Ministry of Environment and Water of the Republic of Bulgaria, the Institute of Oceanology and the Institute of Biodiversity and Ecosystem Research at the Bulgarian Academy of Sciences, is a multidisciplinary approach that integrates remote sensing, geomorphological, geological and phytocoenological surveys and habitat analysis in GIS environment. The procedure involves seven stages: initial inventory and data collection to processing, classification, and high-resolution mapping of coastal dune habitats. The SDMP aims to support sustainable management and conservation of CD ecosystems by emphasizing low-cost, non-intrusive remote sensing techniques. A pilot application on the “Kavatsi” CD system (Sozopol Municipality, Burgas District) validates the SDMP’s effectiveness in addressing the challenges of dune maintenance and anthropogenic impact. This comprehensive approach ensures accurate data collection and supports the development of sustainable management practices for CD ecosystems. The proposed procedure offers a significant step forward to the systematic mapping of CD habitats, responding to the urgent need for effective conservation strategies in the face of significant degradation due to human activities. The SDMP thus plays a crucial role in the sustainable management and conservation of the Bulgarian Black Sea CDs.